‘Shark in the Fish Tank’: Secrets and Stigma in Relational Desistance from Crime - Gålnander, Robin (The British journal of criminology, 2020)
Processes of desistance from crime are intricate and, aside from concrete non-offending, they involve a change in self-perception and an acceptance and recognition of reform by others. A criminalized lifestyle often comes with significant stigma, which together with segregation or exclusion from conventional society can render the procurement of such acceptance and recognition difficult. This article is based on findings from repeated in-depth interviews with desisting women who are just setting out to approach mainstream society. Focusing on the women’s experiences of managing concealable stigma when (re)turning to conventional society, the analysis advances the understanding of individual reform with a focus on relational aspects of desistance from crime.